TRADUCIR Y PUBLICAR EN EL SUR GLOBAL. EL PROGRAMA SUR DE TRADUCCIONES Y LA DIFUSIÓN DE OBRAS DE AUTORES/AS ARGENTINOS, 2010-2022. - Dujovne, Alejandro (Revista Chilena de Literatura, 2024)
Currently, national public programs supporting book translation stand as the most widespread cultural policy tool globally, aiming to enhance the visibility and circulation of a country's literary and intellectual production within a highly competitive and asymmetric global publishing market. For peripheral publishing markets, such initiatives provide visibility on the international cultural stage. Over the past fifteen years, Argentina, Brazil, Colombia, Chile, Mexico, and Uruguay have each established their own support mechanisms. This article focuses on a specific case, Argentina's Programa Sur de Traducciones, examining its impact on disseminating works by Argentine authors in the global South. Distinguished by its long-standing tradition, stability, and substantial volume of subsidized translations, the Sur Translation Program allows for an analysis of the possibilities and limitations of such instruments within a context marked by the dual conditioning factors of the Spanish language's position in the global translation system and the Argentine publishing market's relationship to the Spanish-speaking world, centered around Spain. By examining the dynamics of translating Argentine works to regions and countries seemingly more 'distant' due to their languages' positions in the global translation system, the article explores the extent to which public translation support policies, particularly the Sur Program, effectively mitigate the logics underlying the global market. The study analyzes the support provided by the Sur Program to global South countries from its beginning in 2009-2010 until 2022, through a combined approach involving statistical analysis, the review of editorial profiles, and, in specific cases, interviews with editors.